PENGARUH SELEKSI, PELATIHAN DAN EVALUASI KINERJA TERHADAP EFEKTIVITAS PENGAJARAN GURU DI SMK PERSADA HUSADA INDONESIA - Muhammad Fadly Mawaridz; Abdul Ghofar (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2025)
A good teacher is one who can carry out learning activities effectively and efficiently. Effective teacher teaching can be achieved if the selection, training, and performance evaluation processes are carried out correctly and according to procedures. Implementing selection and training within an organization can produce competent and high-quality teachers who are expected to provide a competitive advantage. The purpose of this study was to determine and analyze the influence of selection, training, and performance evaluation on the teaching effectiveness of teachers at SMK Persada Husada Indonesia. The research design used a quantitative descriptive method. The sample used was 38 people, using census sampling techniques with multiple regression analysis. The results showed that: First, selection had a strong and significant effect on the teaching effectiveness of teachers at SMK Persada Husada Indonesia. Second, training had a strong and significant effect on the teaching effectiveness of teachers at SMK Persada Husada Indonesia. Third, performance evaluation had a strong and significant effect on the teaching effectiveness of teachers at SMK Persada Husada Indonesia. Fourth, selection, training, and performance evaluation had a very strong and significant effect on the teaching effectiveness of teachers at SMK Persada Husada Indonesia.